EXPERIMENTAL SHOCK METAMORPHISM OF THE MURCHISON CM CARBONACEOUS CHONDRITE - IMPLICATIONS FOR PLANETARY ACCRETION - Tomeoka K.; Yamahana Y.; Sekine T. (My University, 1999)
A series of shock-recovery experiments were carried out on the Murchison CM carbonaceous chondrite by using a single-stage propellant gun. The Murchison samples were shocked in nine experiments at peak pressures from 4 to 49 GPa. The recovered samples were studied in detail by using an optical microscope, a scanning electron microscope and an electron-probe microanalyzer.Chondrules are flattened in the plane of the shock front at 4 to 30 GPa. The mean aspect ratio of chondrules increases from 1.17 to 1.57 roughly in proportion to the intensity of shock pressure up to ~25 GPa. At 25 to 30 GPa, the mean aspect ratio does not increase further, and chondrules show increasingly more random orientations and degrade their preferred orientations, and at ~35 GPa, they are extensively disrupted. Most coarse grains of olivine and pyroxene are irregularly fractured, fracture density increases with increasing shock pressure and at ~30 GPa almost all are thoroughly fractured with subgrains of <1 to 5 μm in size. At ~20 GPa, subparallel fractures begin to form in the matrix in directions roughly perpendicular to the compression axis and their densities increase with pressure, especially dramatically at 25 to 30 GPa; thus, the sample is increasingly comminuted and becomes fragile.Local shock melting occurs as melt veins and pockets at 20 to 30 GPa. Fracture-filling veins of fine grains of matrix are also produced at 25 to 30 GPa. The melts and the fine grains seem to result mainly from frictional heating due to displacement along fractures. At ~35 GPa, melting occurs pervasively throughout the matrix. The melts are mainly produced from the matrix; however, they are consistently more enriched in Fe, S, and Ca, which indicates that these elements are selectively incorporated into the melts. The melts contain tiny spherules of Fe-Ni metal, Fe sulfide, and numerous vesicles. At 49 GPa, the matrix is totally melted and coarse grains of olivine are partially melted. The melts contain much larger vesicles (50-300 μm in diameter) than those in the samples shocked at lower pressures, which indicates that much more intense devolatilization and gas expansion took place.For the purpose of comparing shock thermal effects between the experimentally shocked samples and naturally shocked targets (surface materials in the Murchison parent body), we calculated internal energy increase for compression by multiple shock wave reflections (experimental case) and for compression by a single shock wave (natural case). The results suggest that postshock thermal effects observed at each experiment may be attained by impact on the natural targets at a considerably lower shock pressure than the peak shock pressure. From the results of our experiments and calculations, we conclude that if the Murchison parent body were shocked on the surface at pressures higher than ~25 GPa, shocked material would probably undergo drastic increase in the degree of comminution and simultaneous generation of strong expansive forces on pressure release. Thus the results support the hypothesis of Scott et al. (1992) that volatile-rich carbonaceous chondrites shocked above 20 to 30 GPa escaped from the parent body and formed particles that are too small to survive as meteorites.